Sistema Traductor de Lengua Natural a Lengua de Señas para Asegurar la Inclusión Educativa de las Personas con Discapacidad Auditiva de la Unidad Educativa Isabela Católica - Mora Filian, Elmer Javier (2018)
The present project is represented in a prototype application for mobile devices to support a teaching model in different users. To carry out this objective, we will analyze the main aspects towards which the project is directed, which are the students with hearing problems. The application will get information on how recurrent users make use of the app. The functionality of the mobile prototype application will be interpreted dynamically by means of an image in response to the description of a specific phrase with recurrent to the most used by children in their school stage, in order to use the application should be considered that makes use of an authentication system integrated by means of a web service, it is necessary to have internet connectivity to achieve the access procedure and to make use of the functions it has, another function is to generate an audio output to interpret a text, this option is for the person who has the hearing disability in order to communicate by writing in the prototype application what you want to say during a conversation, you should consider that the application is only functional is high-end phones that handle API 22 exclusively. The objective of the project will be illustrated primarily in the result obtained in the learning of sign language within the Isabela Catholic education unit after having used the prototype created especially to teach such language and the involvement of the student community, studying in their new environment of educational equality and cooperativity among students who have a hearing disability and those who do not. To carry out the development of the application, it must be taken into account that, within the mobile device market, the ones that are experiencing the greatest sales growth are tablets and smartphones. The latter will be used to create the application mentioned above, since they have obtained a good acceptance in the market. At present, around 62% of mobile phones are smartphone, which allows greater strength in the use of the developed prototype application. In addition, it achieves the integration of a user-friendly graphic interface. Within the smartphone market you can highlight different operating systems such as: Android, iOS, RIM and Symbian. The mobile operating system chosen for the prototype application to be made is Android.